Internalisasi Nilai Pendidikan Sosial dalam Menumbuhkan Kepedulian Sosial Siswa Kelas VII SMPN 1 Kunjang Kediri - Arsyad Rizal Arfiansyah; Bagus Setiawan (Jurnal Pendidikan Dirgantara, 2026)
The moral crisis and the decline in students' social awareness encourage education to focus not only on academics but also on character development. The internalization of social education values is important for fostering empathy, responsibility, and social sensitivity. At SMPN 1 Kunjang, undisciplined behavior and low levels of social concern indicate the need for a more effective internalization strategy. This study aims to explore the process of internalizing social education values and the supporting and inhibiting factors among seventh-grade students at SMPN 1 Kunjang. The research method used is a descriptive qualitative approach, with the research location at SMPN 1 Kunjang. Data were collected through observation, interviews, and documentation. The results show that the internalization of social education values at SMPN 1 Kunjang is carried out through habituation, role modeling, school rules, and routine activities that cultivate students' empathy and responsibility. Supporting factors include teacher role modeling, routine school programs, and a culture of discipline. Meanwhile, inhibiting factors include weak family roles, negative peer influence, and lack of discipline.